Large area APDs for low energy X-ray detection in intense magnetic fields - Boucher, M. (2003)
An experiment to measure the energy difference between the 2S-2P atomic levels (Lamb shift) in muonic hydrogen is being prepared at PSI. Since the energy levels of muonic hydrogen are a factor of 186 more energetic than those of hydrogen, according to the ratio of reduced masses, the transitions lie in the soft X-ray region. The experiment needs long-lived muonic hydrogen in the 2S state. This is achieved by stopping a low energy muon beam in a small volume of low pressure hydrogen in a 5 T magnetic field. A pulsed beam from a tunable laser induces the 2S-2P transition and the 1.9 keV X-ray photons resulting from the 2P-1S deexcitation will be detected. Measuring the coincidences between the laser pulse and the X-ray as a function of the laser wavelength allows us to determine the Lamb shift. In this presentation we will discuss the perspectives of using large area avalanche photodiodes for the direct detection of the X-rays. Compared to gaseous detectors, they are more compact and simpler in operation. They are also insensitive to magnetic fields.